118k views
1 vote
Write a basic notation for


a = ((b + d))/(2c)

z = (x)/(y + c)

c = (9c + 32)/(5)







User Seiti
by
5.7k points

1 Answer

3 votes

Answer:


a = (b + c)/(2 * c)


z = x/(y + c)


c = (9 * c + 32)/5

Step-by-step explanation:

Required

The expression in basic

To do this, we use () to group items, / as divide and * to combine factors

So, we have:


(a)\ a = ((b + d))/(2c)

In basic, it is:


a = (b + c)/(2 * c)


(b)\ z = (x)/(y + c)

In basic, it is:


z = x/(y + c)


(c)\ c = (9c + 32)/(5)


c = (9 * c + 32)/5

User Mark Chorley
by
4.6k points